EVALUACIÓN DE INDUCTORES DE RESISTENCIA ADQUIRIDA (IRA) SOBRE EL COMPLEJO MANCHA DE ASFALTO EN EL CULTIVO DE MAÍZ (Zea mays L.) EN LA PARROQUIA CARACOL, DEL CANTÓN BABAHOYO. - EZETA FLORES HECTOR (2025)
Corn is an agricultural product that is produced mostly in the world. According to its nutritional qualities to produce animal protein, human consumption, and industrial use, it has become one of the most important products in international markets. In Ecuador many families are dedicated to this activity, being Los Ríos where 45% of the country's production is concentrated. Science has long wondered how to activate a plant's defense system where and when it is needed, a field in which a breakthrough has just taken place. Because plants have a deficient immune system, it is necessary to generate mechanisms that increase these systems, it is necessary to use tools to produce plants, however, the appearance of new concepts of plant fungal control has allowed the flourishing of a new line of physiological activators. The objective of the research is to evaluate inducers of acquired resistance (IRA) on the asphalt stain complex in corn cultivation. The investigation was carried out on the grounds of the Hacienda "La Suerte", province of Los Ríos. In this study, the maize hybrid of the simple type Emblema was used. In the field work, an experimental design of "randomized complete blocks (BCA)" was used. The treatments were: salicylic acid, chitin, Peptide-Gramicidin, Poly-Glucosarine, Fosetyl Aluminum and a Control, all of them in two doses and applications, at 20 and 35 days after sowing. It was assessed: Incidence and severity of the disease with formulas, and severity of the disease with a diagrammatic scale. In addition, agronomic variables related to crop production were evaluated. The presence of grain spotting disease (Phyllachora maydis, Monographella maydi, Coniothyrium phyllachorae) was evident in the evaluation area. The application of physiological resistance activators generated control over the appearance of asphalt staining, compared to the control which was severely attacked. The application of salicylic acid 1.0 l/ha registered the least damage of the disease in all the evaluations. The highest production was achieved by applying salicylic acid asphalt stain control at 1,0 l/ha with 10166,67 kg/ha, the control had the worst average yield (4846,67 kg/ha).